1983
DOI: 10.1203/00006450-198306000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Cheverly: an Unstable Hemoglobin Associated with Chronic Mild Anemia

Abstract: SummaryThe evaluation of a family with chronic mild anemia led to the identification of a new unstable hemoglobin (Hemoglobin Cheverly). Modest anemia and reticulocytosis, normal to slightly increased mean corpuscular volume (MCV), and normal mean corpuscular hemoglobin concentration (MCHC) were present in the affected family members. Electrophoresis of blood samples on cellulose acetate and on citrate agar revealed normal patterns. Globin chain analysis and isoelectric focusing data were also normal. After in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Another case in 1983 involved a family of three from Baltimore with chronic mild anaemia. 5,6 An observational study done in Germany showed that only 9 out of 34,228 persons had Hb Cheverly. 7 Hb Cheverly is caused by point mutation with the replacement of thymidine by cytosine and subsequently the substitution of the amino acid phenylalanine (Phe) by serine (Ser) at the CD4 region in the haem pocket, at codon 45 of the beta globin chain.6 This weakens the Hb interaction, rendering the instability of the mutated beta globin chain, leading to a mild haemolytic anaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another case in 1983 involved a family of three from Baltimore with chronic mild anaemia. 5,6 An observational study done in Germany showed that only 9 out of 34,228 persons had Hb Cheverly. 7 Hb Cheverly is caused by point mutation with the replacement of thymidine by cytosine and subsequently the substitution of the amino acid phenylalanine (Phe) by serine (Ser) at the CD4 region in the haem pocket, at codon 45 of the beta globin chain.6 This weakens the Hb interaction, rendering the instability of the mutated beta globin chain, leading to a mild haemolytic anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…At our hospital, her pulse oximetry consistently showed readings below 85%. However, an arterial blood gas analysis Clinical A family of three with haemoglobin Cheverly: low oxygen saturation in stable patients Lai Chee Chow 1 , Soo Huan Puah 2 , Xun Ting Tiong 3 , Nisha Sabrina Aloysious 4 , Tze Shin Leong 5 , Lee Ping Chew 6 showed good oxygenation with partial pressure of oxygen in arterial blood (PaO 2 ) of 554.9 mmHg under HFMO2 15 L/ min and PaO 2 of 99.3 mmHg under room air. The arterial oxygen saturation (SaO 2 ), methaemoglobin (metHb) and carboxyhaemoglobin (COHb) were normal.…”
Section: Case Presentationmentioning
confidence: 99%
“…Most of the qualitative hemoglobinopathies have frequencies below 1% and can be associated with various or even no clinical manifestations [8]. In 1982 and 1983, an elderly Italian male with cyanotic heart disease [9] and an anemic female in Baltimore [10] were the first patients described with the Cheverly variant hemoglobin. In a German observational study, over a period of four decades, only 9 patients within hemoglobin Cheverly have been found [11].…”
Section: Discussionmentioning
confidence: 99%